Nucleic acid vaccination strategies for ovarian cancer - Saha, Chayanika; Bojdo, James; Dunne, Nicholas J.; Duary, Raj Kumar; Buckley, Niamh; McCarthy, Helen O. (Frontiers in Bioengineering and Biotechnology, 2022)
High grade serous carcinoma (HGSC) is one of the most lethal ovarian cancers that is characterised by asymptomatic tumour growth, insufficient knowledge of malignant cell origin and sub-optimal detection. HGSC has been recently shown to originate in the fallopian tube and not in the ovaries. Conventional treatments such as chemotherapy and surgery depend upon the stage of the disease and have resulted in higher rates of relapse. Hence, there is a need for alternative treatments. Differential antigen expression levels have been utilised for early detection of the cancer and could be employed in vaccination strategies using nucleic acids. In this review the different vaccination strategies in Ovarian cancer are discussed and reviewed. Nucleic acid vaccination strategies have been proven to produce a higher CD8+ CTL response alongside CD4+ T- cell response when compared to other vaccination strategies and thus provide a good arena for antitumour immune therapy. DNA and mRNA need to be delivered into the intracellular matrix. To overcome ineffective naked delivery of the nucleic acid cargo, a suitable delivery system is required. This review also considers the suitability of cell penetrating peptides as a tool for nucleic acid vaccine delivery in Ovarian Cancer.